1989
DOI: 10.1007/bf00934152
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mediolateral deformity, tibial torsion, and foot position on femorotibial load

Abstract: The influence of mediolateral deformity, tibial torsion, and different centers of foot support was studied with a three-dimensional computer model that incorporates the significant muscles of the lower extremities needed for quasi-static walking. This theoretical method avoids the variability in gait pattern from the pain and discomfort associated with deformity in patients. The study illustrates the possible importance of the muscle force on the load across the knee and ankle. High strains in the medial gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…We have previously reported that people with knee OA have greater tibial internal rotation compared to aged-matched controls [35], and a reduction in tibial internal rotation was observed in patients who underwent realignment of the knee following knee replacement surgery [35]. Furthermore, internal torsion and varus deformity have been associated with increased loads on the medial compartment of the knee [36]. The lack of correlation in the present study between tibia rotation and KAMs may be related to a possible restriction in tibial motion as patients may be "pushed" to the end range of motion due to years of walking in the same pattern.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that people with knee OA have greater tibial internal rotation compared to aged-matched controls [35], and a reduction in tibial internal rotation was observed in patients who underwent realignment of the knee following knee replacement surgery [35]. Furthermore, internal torsion and varus deformity have been associated with increased loads on the medial compartment of the knee [36]. The lack of correlation in the present study between tibia rotation and KAMs may be related to a possible restriction in tibial motion as patients may be "pushed" to the end range of motion due to years of walking in the same pattern.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated a small internal tibial torsion of less than 20 o might be biomechanically beneficial to people with moderate KOA. However, since none of our subjects had excessive internal tibial torsion, it cannot be ruled out that higher internal tibial torsion might increase the medial compartment load [26]. Also, tibial torsion was strongly associated with foot progression angle in the adult population [27].…”
Section: Plos Onementioning
confidence: 80%
“…Recent research on cartilage forces and associations between variations in anatomy around the hip and leg alignment might better explain why cartilage in lateral OA deteriorates more rapidly in specific patients. 11,[14][15][16][17][18][19][20][21][22][23][24] Deformity analysis will help find the patient in which a valgus leg deformity is caused by a femoral deformity. Paley 25 describes a comprehensive system of measurements of bones and joint line angles, and defines that a femoral valgus deformity is present when the so-called mLDFA (mechanical lateral distal femoral angle) is < 88 degrees.…”
Section: Wylie Et Al (2016)mentioning
confidence: 99%